การคำนวณเชิงตัวเลขของการไหลแบบราบเรียบโดยใช้ระเบียบวิธีไฟไนต์วอลุมในพิกัดกระชับขอบเขต - ณัฐพล โชคบุญมงคล (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
To present a finite volume method based on the body-fitted coordinates (BFC) for solving laminar flow problems with complex geometries. The work can be divided into two parts : grid generation and the finite volume method. For the grid generation part, the initial grid is generated by the transfinite interpolation (TFI). Geometric coefficients are calculated from this part. For the finite volume method, the computational space is used for calculation. The governing equations in Cartesian coordinates must be transformed into those in body-fitted coordinates and then discretized by the finite volume method. Finally, the algebraic equation system is solved by the line-by-line TDMA method. The computer program is validated by solving simple problems, of which exact solutions or other numerical results are available. The validate cases are flow in parallel channel, flow in gradual-expansion channel, flow in sinusoidal and flow in wave-wall. The accurate results show that the finite volume method based on body-fitted coordinates can accurately solve problems in complex geometries.